2016
DOI: 10.1515/znc-2016-0119
|View full text |Cite
|
Sign up to set email alerts
|

Virus inactivation under the photodynamic effect of phthalocyanine zinc(II) complexes

Abstract: Various metal phthalocyanines have been studied for their capacity for photodynamic effects on viruses. Two newly synthesized water-soluble phthalocyanine Zn(II) complexes with different charges, cationic methylpyridyloxy-substituted Zn(II)- phthalocyanine (ZnPcMe) and anionic sulfophenoxy-substituted Zn(II)-phthalocyanine (ZnPcS), were used for photoinactivation of two DNA-containing enveloped viruses (herpes simplex virus type 1 and vaccinia virus), two RNA-containing enveloped viruses (bovine viral diarrhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…For example, the early work by Horowitz et al using aluminum phthalocyanine derivatives (AIPc; AIPc-chloride, AIPcdisulfonate, AIPc-tetrasulfonate) showed an efficient inactivation of both cell-associated and cell-free enveloped vesicular stomatitis virus (VSV) and human immunodeficiency virus 1 (HIV-1), but not non-enveloped encephalomyocarditis virus (EMCV) in whole blood, with minimal damage to red blood cells (RBC) (Horowitz et al 1991;Smetana et al 1994;Ke et al 2014). Whereas this study suggested that the virus envelope was the major target for inactivation, Reminchkova et al observed equally efficient inactivation of cell-free enveloped HSV-1 and vaccinia virus (VV) with cationic and anionic phthalocyanine Zn(II) complexes-PDT, but found rather striking differences between these two compounds on the enveloped bovine viral diarrhea virus (BVBV) (Remichkova et al 2016). Both compounds were largely ineffective in inhibiting enveloped Newcastle disease virus (NDV), and non-enveloped Coxsakie virus B1 and human adenovirus type 5 (ADV5).…”
Section: Antiviral Pact and Phthalocyaninesmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, the early work by Horowitz et al using aluminum phthalocyanine derivatives (AIPc; AIPc-chloride, AIPcdisulfonate, AIPc-tetrasulfonate) showed an efficient inactivation of both cell-associated and cell-free enveloped vesicular stomatitis virus (VSV) and human immunodeficiency virus 1 (HIV-1), but not non-enveloped encephalomyocarditis virus (EMCV) in whole blood, with minimal damage to red blood cells (RBC) (Horowitz et al 1991;Smetana et al 1994;Ke et al 2014). Whereas this study suggested that the virus envelope was the major target for inactivation, Reminchkova et al observed equally efficient inactivation of cell-free enveloped HSV-1 and vaccinia virus (VV) with cationic and anionic phthalocyanine Zn(II) complexes-PDT, but found rather striking differences between these two compounds on the enveloped bovine viral diarrhea virus (BVBV) (Remichkova et al 2016). Both compounds were largely ineffective in inhibiting enveloped Newcastle disease virus (NDV), and non-enveloped Coxsakie virus B1 and human adenovirus type 5 (ADV5).…”
Section: Antiviral Pact and Phthalocyaninesmentioning
confidence: 93%
“…(Horowitz et al 1991;Rywkin et al 1992Rywkin et al , 1994Rywkin et al , 1995Gaspard et al 1995;Remichkova et al 2016;Rodrigues et al 2016b). In most of these studies, a significant decrease in virus infectivity was observed with a variety of different phthalocyanine derivatives.…”
Section: Antiviral Pact and Phthalocyaninesmentioning
confidence: 99%
“…7,8,9 Phthalocyanines have been evaluated for the PDI of a large number of viruses, among them most prominently VSV, HSV, and HIV. They showed high activity against these and other enveloped viruses 289,290,291,292 but were in general found not to be active against non-enveloped viruses, 289,290,292 suggesting that the viral envelope is a main target of the ROS generated. However, the non-enveloped human rhinovirus type 5 (RV-5) was successfully photoinactivated with a sulfonated naphthabenzoporphyrazine.…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…In addition, it was found to be secure with low toxicity [60]. Zinc was also found to have a strong photocytotoxic antiviral activity especially on enveloped viruses such as herpes simplex type 1 and influenza virus [61][62][63]. In a case series, wherein 50 mg zinc sulfate supplements were given daily for two to three months to three cases of oral dysgeusia, symptoms were reduced after one month, leading the authors to conclude that zinc deficiency may be one of the causes of taste disorders [64].…”
Section: Benefits Of Zinc Treatment In Oral Diseasesmentioning
confidence: 99%